The LATS2 tumor suppressor inhibits SREBP and suppresses hepatic cholesterol accumulation - Aylon, Yael; Gershoni, Anat; Rotkopf, Ron; Biton, Inbal E.; Porat, Ziv; Koh, Anna P.; Sun, Xiaochen; Lee, Youngmin; Fiel, Maria-Isabel; Hoshida, Yujin; Friedman, Scott L.; Johnson, Randy L.; et al. (Genes & development, 2016)
The Hippo signaling pathway is a major regulator of organ size. In the liver, Hippo pathway deregulation promotes hyperplasia and hepatocellular carcinoma primarily through hyperactivation of its downstream effector, YAP. The LATS2 tumor suppressor is a core member of the Hippo pathway. A screen for LATS2-interacting proteins in liver-derived cells identified the transcription factor SREBP2, master regulator of cholesterol homeostasis. LATS2 down-regulation caused SREBP activation and accumulation of excessive cholesterol. Likewise, mice harboring liver-specific Lats2 conditional knockout (Lats2-CKO) displayed constitutive SREBP activation and overexpressed SREBP target genes and developed spontaneous fatty liver disease. Interestingly, the impact of LATS2 depletion on SREBP-mediated transcription was clearly distinct from that of YAP overexpression. When challenged with excess dietary cholesterol, Lats2-CKO mice manifested more severe liver damage than wild-type mice. Surprisingly, apoptosis, inflammation, and fibrosis were actually attenuated relative to wild-type mice, in association with impaired p53 activation. Subsequently, Lats2-CKO mice failed to recover effectively from cholesterol-induced damage upon return to a normal diet. Additionally, decreased LATS2 mRNA in association with increased SREBP target gene expression was observed in a subset of human nonalcoholic fatty liver disease cases. Together, these findings further highlight the tight links between tumor suppressors and metabolic homeostasis.